تصنيف الجامعات الخضراء وتحسين استدامة الحرم الجامعى فى مصر Ranking Green Universities and Improving Campus Sustainability in Egypt - Lobna Agha (Journal of Engineering Research - Egypt)
The Egyptian state attaches great importance to the advancement of university education through the development of Egyptian universities and placing them in advanced centers, as the state seeks to transform universities from a consumer of knowledge into a producer of it, while achieving compatibility between disciplines and the labor market, and this is what the higher education strategy and Egypt's vision 2030 are based on. Egypt has a large number of public universities, private universities, and private universities, numbering 66, of which 17 were applied to UI Green Metric in 2022.The aim of this study is to analyze the performance of the UI Green Metric classification of universities in Egypt and to provide suggestions for increasing the number of Egyptian green universities and becoming environmentally friendly campuses. The data used in the study is taken from the official website of the Green Metric classification. The higher and lower categories will be identified.The most successful category was “Energy and Climate (EC)” and Waste (WS) while the most unsuccessful category was “Water (WR)” in Egypt. In addition, 74% of Egyptian universities did not participate in the ranking. The main problems are the lack of sustainability offices and the inability to provide institutional data for the application. It was proposed to save institutional data, the monitoring system, and target global indicators such as the sustainable development goals in order to become a university campus.